Optimizing sustainable ecotourism management for aquatic ecosystem preservation and fishermen empowerment: A descriptive and exploratory research - Armayadi, Dedy; Afifah, Nadia; Rifai, Rizal (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Ecotourism has significant potential to support the sustainability of aquatic ecosystems while also providing economic and social benefits to fishing communities in coastal areas. This study focuses on optimizing sustainable ecotourism management to support the preservation of aquatic ecosystems and empower fishermen in Raja Ampat Regency. Methods: The research is descriptive and exploratory, aiming to describe and analyze the existing facts, phenomena, or situations related to sustainable ecotourism management. Data collection techniques include observation and the analysis of literature and documents relevant to the research topic. Findings: The study suggests that the integration of education and ecology through the EduEco Tourism concept can help preserve the region's ecological integrity while benefiting local communities. The concept also emphasizes fostering responsibility among visitors. Conclusion: Sustainable ecotourism, supported by effective policies and fishermen empowerment, plays a key role in preserving aquatic ecosystems and improving the livelihoods of local communities. The EduEco Tourism model offers a balanced approach to environmental conservation and community development in Raja Ampat. Novelty/Originality of the Study: This study highlights the dual role of ecotourism in preserving aquatic ecosystems while simultaneously fostering the socio-economic empowerment of local fishing communities, offering policy recommendations for more sustainable management practices.